The Role of Digital Platforms in Developing Entrepreneurship: A Bibliometric Analysis - Loso Judijanto; Johni Eka Putra; Haruni Ode; Elkana Timotius; Supriandi Supriandi (Westscience Press, 2024)
The rapid advancement of digital technology has significantly transformed the entrepreneurial landscape, offering unprecedented opportunities and posing new challenges. This study employs a bibliometric analysis to explore the role of digital platforms in developing entrepreneurship. The analysis identifies key thematic clusters such as entrepreneurial ecosystems, digital marketing, and social entrepreneurship, highlighting their interconnectedness and impact on entrepreneurial activities. Recent research trends emphasize the implications of the Covid-19 pandemic and the potential of emerging technologies like the metaverse. Identified research opportunities in less explored areas, such as digital artifacts, digital skills, and e-commerce, suggest directions for future investigation. Additionally, the author collaboration network reveals strong intra-group collaborations with scope for increased interdisciplinary research. This comprehensive overview provides valuable insights into the current state and future potential of digital entrepreneurship, guiding scholars and practitioners in navigating this dynamic field.